Pas de deux: The complicated relationship between cooperating teachers and pre-service teachers - Parks, Philippa (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2023)
The practicum experience is a crucial moment of learning for a pre-service teacher (PST). At the heart of the experience is the relationship PSTs have with their cooperating teachers (CTs). To examine how this relationship was negotiated during the practicum, this article applied Cortazzi’s analysis of narrative approach to stories told by 13 PSTs, stories that comprised part of a larger mixed-method study. Findings from analysis of the more than 200 narratives told by the 13 PSTs disclosed the several ways in which PSTs experienced support from their CTs, including planned introductions of the PST to the classroom students, the CT’s explicit support of PST decisions, and a negotiated withdrawal of the CT’s presence.